2012
DOI: 10.1177/1753193412469580
|View full text |Cite
|
Sign up to set email alerts
|

The long-term follow-up of treatment with corticosteroid injections in patients with carpal tunnel syndrome. When are multiple injections indicated?

Abstract: The objective of this prospective study was to investigate the long-term effect of one or more local corticosteroid injections in patients with carpal tunnel syndrome and whether a good response can be predicted. Follow-up visits took place at 3 weeks, 6 months, and 1 year after the first corticosteroid injection. Thirty of the 120 patients (25%) had a good outcome with a single injection, 11 additional patients (9%) needed a second injection, and five patients (4%) needed a third injection to reach a good out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
1
20
1
1
Order By: Relevance
“…The proportion is lower than in our study, but their result was based on patients with mild to moderately severe CTS only. Berger et al found that 75% underwent surgery after a single injection, a slightly higher proportion than our result (10). In that prospective study patients were offered a re-injection or surgery when there was minor or no relief of symptoms at follow-up, which might have resulted in a higher proportion of injection failure.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The proportion is lower than in our study, but their result was based on patients with mild to moderately severe CTS only. Berger et al found that 75% underwent surgery after a single injection, a slightly higher proportion than our result (10). In that prospective study patients were offered a re-injection or surgery when there was minor or no relief of symptoms at follow-up, which might have resulted in a higher proportion of injection failure.…”
Section: Discussioncontrasting
confidence: 79%
“…They found that the change in Boston Symptom Severity Scale and Functional Status Scale was not significantly different between first and second injections and concluded that second injections appear to be at least as effective as first injections. To the best of our knowledge, the maximum number of injections that an individual might benefit from is unknown (10). …”
Section: Discussionmentioning
confidence: 99%
“…However, among them, symptoms had recurred in 8 patients at 1 st year, while in 79% of the patients symptomatic regression continued at the end of the first year. In a study performed in Netherlands, the improvement rate at the end of the first year of injectable steroid therapy was reported as 25% (2). Similarly Meys et al emphasized the need for surgery in 67 % of the patients at the end of the first year of injectable steroid therapy (20).…”
Section: █ Resultsmentioning
confidence: 99%
“…11 A recent randomized controlled trial (RCT) also showed that steroid injection provided more benefits than placebo at the 10th week of treatment, but there was no significant difference observed at 1-year follow-up. 12 Only one-third of patients with carpal tunnel syndrome who received steroid injections had longer term benefits 13 and some required an additional 2-3 injections to obtain relief. 13 However, 1 study conducted in Estonia reported that patients who received repetitive steroid injections were more likely to have postoperative symptoms of carpal tunnel syndrome if they eventually opted for surgery.…”
mentioning
confidence: 99%
“…12 Only one-third of patients with carpal tunnel syndrome who received steroid injections had longer term benefits 13 and some required an additional 2-3 injections to obtain relief. 13 However, 1 study conducted in Estonia reported that patients who received repetitive steroid injections were more likely to have postoperative symptoms of carpal tunnel syndrome if they eventually opted for surgery. 14 Acupuncture is commonly used to manage pain and neuropathy in Chinese medicine.…”
mentioning
confidence: 99%